MANAJEMEN MUTU PERGURUAN TINGGI AGAMA ISLAM SWASTA - Bunyamin Bunyamin; Alamsyah Alamsyah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2013)
This paper is intended to describe the Possibility to apply quality management in Private Islamic University (PTAIS) in Indonesia. The method used to analysed this is content analysis. The theory used is the theory of total quality management (TQM) which is adapted with PTAIS institutional conditions. The findings showed that The strategy to develop the quality of Private islamic Universities should be, at least: 1) directed to The development of academic quality based on internaitonal standard, so that the academic and social needs for national and regional scale is automatically able to be met, 2) supported by a good academic atmosphere so that attempts to improve the academic quality can be run more quickly and effectively; 3) the primary support to the internationalization of Islamic education which is more humane; and establish broad international academic networking to support the human resources quality which is more superior, innovative, and productive.